If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -2 = 0 Reorder the terms: -2 + 2y = 0 Solving -2 + 2y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 2y = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 2y = 0 + 2 2y = 0 + 2 Combine like terms: 0 + 2 = 2 2y = 2 Divide each side by '2'. y = 1 Simplifying y = 1
| 3w^2-24w^2+36=0 | | 8x^2+72x^2+64x= | | t^2-14t+49=0 | | 7x-3-2x=8+4 | | 4x^2-27x+39=-3x+4 | | (9x+15)(8x+15)=0 | | -x+10+5x=26 | | ((3x^2)-3)*((3x^2)-3)=0 | | x^7-256x^2= | | x^2+3x=2x+2 | | -3+-x+3x=-25 | | x^8-x^4= | | x^2-12x+36=9 | | 8x^3+4x^2-y^2-y^3=0 | | x^2+x-2= | | 8(3x+10)=28x(-14)-4x | | 12x+4y=80 | | x^7-256x^3= | | x^2-x-12=2x-2 | | x^2-x-10=10 | | 12x-7=11(x+9)-1 | | 10x-5=9(x+7)+10 | | 4t^2-19t-30=0 | | 3(x-12)-5=16x-93 | | 6x+0.2=4x-0.8 | | 11(x-9)-10=32x-298 | | 6x+0.2=4x-(-0.8) | | X^2-3x-54=(x+6) | | 7x-1=5x-33 | | 7x^2-6=2x | | N^2+20n+91=0 | | 6p=-2+3(1-p) |